Can Coalho cheese lactic microbiota be used in dairy fermentation to reduce foodborne pathogens? - Dias, Giselle Maria Pereira; Silva, Adriano Barbosa da; Granja, Nathalia Maria Cavalcanti; Silva, Talitha Nóbrega da; Lima, Gileno Vitor Mota; Cavalcanti, Maria Taciana Holanda; Porto, Ana Lúcia Figueiredo (Scientia Plena, 2019)
In order to study the biodiversity of lactic acid bacteria (LAB) and evaluate their potential for use in dairy fermentation to inhibit foodborne pathogens, we collected two types of Coalho cheese made with raw milk from an artisanal production located in Venturosa, Agreste Region in the state of Pernambuco. From 480 isolates, 210 (Gram-positive; catalase-negative; able to clot skim milk) were identified as LAB and 78 were identified at genus level. The genera found were Enterococcus (37.1%), Streptococcus (25.6%), Lactococcus (19.2%) and Leuconostoc (15.3%). The technology potential showed that most of the LAB exhibited proteolytic activity (82.9%), diacetyl production (65.7%), grown in 3, 4 and 6.5% NaCl (more than 50%), and rapidly acidified milk (52.6%) due to the production of lactic acid. The antagonistic potential showed that most LAB inhibited the growth of Staphylococcus aureus ATCC 6538 (82.89%) and Escherichia coli ATCC 25922 (88.15%), and 72.36% of the LAB presented antimicrobial activity against the two indicators. Among the Enterococcus strains, most (more than 70%) were gama-hemolitic and none produced gelatinase. This study allowed for the selection of strains with promising potential for use in dairy fermentation that could reduce the contamination of milk and cheese by foodborne pathogens.